Molecular Characterization of African Swine Fever Viruses from Outbreaks in Peri-Urban Kampala, Uganda - Frank Norbert Mwiine; Joseph Nkamwesiga; Christian Ndekezi; Sylvester Ochwo (Advances in Virology)
African swine fever (ASF) is an infectious transboundary disease of domestic pigs and wild swine and is currently the most serious constraint to piggery in Uganda. The causative agent of ASF is a large double-stranded linear DNA virus with a complex structure. There are twenty-four ASFV genotypes described to date; however, in Uganda, only genotypes IX and X have been previously described. Inadequate ASF outbreak investigation has contributed to the delayed establishment of effective interventions to aid the control of ASF. Continuous virus characterization enhances the understanding of ASF epidemiology in terms of viral genome variations, extent, severity, and the potential source of the viruses responsible for outbreaks. We collected samples from pigs that had died of a hemorrhagic disease indicative of ASF. DNA was extracted from all samples and screened with the OIE recommended diagnostic PCR for ASF. Partial B646L (p72), full-length E183L (p54) genes, and CVR region of the P72 gene were amplified, purified, and sequenced. Web-based BLAST and MEGA X software were used for sequence analysis. ASF was confirmed in 10 of the 15 suspected pig samples. Phylogenetic analysis confirmed circulation of genotype IX by both full-length E183 (p54) and partial B646L (p72) gene sequencing. Intragenotypic resolution of the CVR region revealed major deletions in the virus genome, in some isolates of this study. The marked reduction in the number of tetrameric tandem repeats in some isolates of this study could potentially play a role in influencing the virulence of this particular genotype IX in Uganda.